2008
DOI: 10.1021/op800010m
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Nondispersive Reactor for Two-Phase Reactions

Abstract: A novel continuous static reactor concept improves mass transfer in two-phase chemical reactions between 1 and 2 orders of magnitude. The current paradigm for chemical reactions between two liquids requires energy-intensive mixing to disperse droplets of one phase in the continuous phase. The new reactor contacts a continuous free phase with a continuous phase constrained to a multitude of fibers. Phases come out of the reactor cleanly separated. An etherification reaction, a dehydrochlorination reaction, a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…To improve the mass transfer between the two phases, vigorous agitation is needed in a conventional batch reactor 13–15. Recently, it was suggested that a microreactor was suitable for use in the transesterification of vegetable oil in the production of BDF 16–20. It was reported that the required reaction time was remarkably reduced when a microreactor was used instead of a batch reactor, suggesting that mass transfer across the boundary of immiscible liquids in a microchannel could be significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mass transfer between the two phases, vigorous agitation is needed in a conventional batch reactor 13–15. Recently, it was suggested that a microreactor was suitable for use in the transesterification of vegetable oil in the production of BDF 16–20. It was reported that the required reaction time was remarkably reduced when a microreactor was used instead of a batch reactor, suggesting that mass transfer across the boundary of immiscible liquids in a microchannel could be significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The data show that these mixing devices allow high conversion rates in short residence times, which are of the order of several minutes. Furthermore, some authors also observed good product separation at the reactor outlet, despite the formation of liquid-liquid emulsions [163].…”
Section: Static Mixers and Other Motionless Inline Devicementioning
confidence: 99%
“…In both reactor designs, the phase contacting via the static mixer and the continual removal of glycerol enhance the reaction and high conversion is obtained in less than 30 min, which is significantly faster than in conventional equipment. Metallic foams and other inserts, such as steel spheres and various types of fibers, have also shown to enhance transesterification reactions [155,[161][162][163]. These devices create tortuous interstices with micron-sized dimensions that promote fluid contacting and mixing, and consequently the chemical reaction.…”
Section: Static Mixers and Other Motionless Inline Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The fifth possibility is a continuous reactor with static mixing. A novel continuous static reactor concept improves mass transfer in two-phase chemical reactions between one and two orders of magnitude (Massingill et al, 2008). The sixth possibility is a film reactor.…”
Section: Continuous Reactorsmentioning
confidence: 99%